Real time astrocyte in spiking neural network - Abdul-Rahman Abed, Bassam; Ismail, Amelia Ritahani; Abdul Aziz, Normaziah (2015)
Astrocytes, one type of glial cells, are considered to be an active partner to neurons in processing information of Central Nervous System (CNS). Therefore, studying the interaction between the astrocytes and neurons is important to create a novel model for Artificial Neuron-Glial Networks (ANGN). In this paper, a novel model for (ANGN) is proposed to model the real time interaction between Astrocytes and neurons by using Spiking Neural Networks (SNNs) and mathematical models for astrocyte-neuron interaction. How could this proposed model will be biologically inspired to model the real time interaction between astrocytes and neurons and to improve the performance of the SNN? However, these mathematical models are generalized and simplified to be used in the proposed network. The performance of the proposed network was compared with standard SNN and the simulation results showed that the proposed model evoked more spikes to fire whenever astrocytes were activating in a time window. This indicates that astrocytes are playing significant roles in processing information of the ANGN.